The Weak Convergence in Hilbert Spaces Concept Construction - Ferreira, M. A. M. (2014)
It is intended in this article to critically review the weak convergence concept in the real Hilbert (Note 1) spaces domain. It is studied mainly its construction process, since the main goal was to generalize the Bolzano (Note 2)-Weierstrass (Note 3) theorem. Then it is discussed in which conditions weak convergence implies convergence.